Contestation of Boarding School Leaders on Transformation of Islamic Education: A Study of Nahdlatul Wathan Education Institution in Lombok - Nur Hamiyetun; Nila Purwati; Meysin Karinap (Innovative Pedagogy and Education Studies, 2024)
This study aims to analyze the dynamics of leadership contestation in Islamic boarding schools and its role in the transformation of Islamic education within Nahdlatul Wathan educational institutions in Lombok. A qualitative approach with a case study design was employed. The participants consisted of boarding school leaders, teachers, and institutional stakeholders selected through purposive sampling. Data were collected through in-depth interviews, participant observation, and institutional document analysis, and were analyzed using thematic analysis. The findings reveal that leadership contestation arises from differences in ideological orientation, educational vision, and authority patterns between traditional charismatic leadership and Islamic transformational leadership that is more adaptive to change. This contestation significantly influences curriculum transformation, institutional governance, and the integration of traditional Islamic education with modern educational systems. The study concludes that leadership contestation, from an Islamic leadership perspective, functions not merely as a source of conflict but as a dialectical mechanism that stimulates dynamic change and renewal in Islamic boarding school education.